Farm-nonfarm labor mobility in rural Bangladesh: Intersectoral shift or intergenerational occupational choice? - Dorosh, Paul A.; Sen, Binayak; van Asselt, Joanna; Ahmed, Mansur (International Food Policy Research Institute, 2018)
The paper argues that much of the farm-nonfarm labor mobility in rural Bangladesh is in nature an intergenerational occupational choice-induced change rather than a sectoral shift within the current generation. Bangladesh has a large share of youth (aged 15-29 years) in the labor force, and it experienced a major structural shift in employment between 1995 and 2010 as agricultural employment fell from 51.4 percent to 42.3 percent. Much of this shift has been due to changes in youth employment, as youth employment in agriculture fell from 49.8 percent to 33.1 percent. The cohort analysis (pseudo-panel) shows that the reduction in the share of male youth population working in agriculture is due mainly to a sharp reduction in the percentage of youth who start out in agriculture, rather than a shift by individuals from agricultural to non-agricultural employment during their life time. Analysis of correlates of the non-farm orientation of rural youth indicates the importance of gender, human capital, access to electricity, proximity to cities, and migration opportunities. The results suggest the importance for supporting rural industry and service activities for meeting the future demand of jobs for the rural youth.